ダイ 30ジ ナンキョク チイキ カンソク タイ エットウ タイイン ノ シンシン リョウメン ヨリ ミタ ケンコウ ジョウタイ ノ スイイ ト ソノ モンダイ テン ニ ツイテ - 高見, 俊司; タカミ, シュンジ; 坂本, 忠成; サカモト, タダシゲ; Takami, Shunji; Sakamoto, Tadashige (1991)
P(論文) 第30次南極観測越冬隊員に対し, 越冬前後と越冬各期間に医学的諸調査を施行し, 特殊環境下での身体的精神的健康状態の推移を検討した。心身調査項目としてCMI調査表, Y-G検査, エゴグラムを使用した。身体的検査項目としては標準12誘導心電図, ホルター24時間心電図, 血圧, 血液一般と血中コルチゾール値を測定した。大きな疾患の発生はなかったが, 全期間を通じてさまざまな心身の愁訴が認められた。精神的には越冬中期で積極性の低下, うつ傾向などが出現し, それらは経時的に変動した。ホルター24時間心電図では昼夜リズムの消失が一部で認められた。血中コルチゾール値は様々な変動を示し, その上昇は何らかのストレスの関与が考えられた。総蛋白, アルブミン, ヘマトクリットはいずれも低下した。それ以外の標準12誘導心電図, 血圧, 血算, 生化学検査には著変は認められなかった。越冬期間中のこれらの変化には気候条件, 太陽リズム, 閉鎖的小集団生活, 食事内容など各種の因子の関与が考えられた。 Medical and psychological investigations were performed on the 30th Japanese Antarctic Research Expedition (JARE-30) wintering members throughout a year. Psychosomatic investigation consisted of CMI, Y-G and Egogram. Physiological investigation consisted of standard 12-induction electrocardiogram, holter long-time electrocardiogram, blood pressure, hematological and biochemical studies, and serum cortisol level. Although no significant disease was experienced throughout the wintering period, various mental and physical complains were observed. The depressive tendency and the decrease of positiveness were seen in the midwinter period. With holter long-time electrocardiogram recordings, the disappearance of the circadian rhythms of heart rate was observed. The elevation of serum cortisol level was observed which suggests the existence of stress-irritation. Serum total protein, serum alubumin, hematocrit and hemogrobin lowered during the wintering period. Other examinations on electrocardiogram, blood pressure, hematological and biochemical studies revealed no significant changes. departmental bulletin paper